Adaptation Strategy Can Ensure Seed and Food Production With Improving Water and Nitrogen Use Efficiency Under Climate Change. Issue 2 (6th February 2023) - Chen, Shichao; Liu, Wenfeng; Yan, Zongzheng; Morel, Julien; Parsons, David; Du, Taisheng
Abstract: Adaptation strategies can reduce the negative impacts of climate change on food security. As an important part of food security, more attention should be paid to seed security, as it determines the crop planting area and ultimately affects food production, especially in major seed production locations, such as the Hexi Corridor in China. This region is an important production base of grain (including field maize and wheat) and maize seed, but the shortage of water resources and low use efficiency of water and nitrogen (N) seriously constrain the sustainable development of agriculture. Formulating an adaptation strategy to balance the seed and food production and resource use efficiency is an important way to maintain regional as well as national food production. We established an optimization‐simulation framework, which consists of a novel crop production function and a grid‐based crop model, APSIM. This framework was used to optimize agricultural management and evaluate its performance considering the spatio‐temporal variability of climate and soil properties, actual crop water consumption and N uptake during each growth stage, and interactive sensitivity coefficients of water and N at different growth stages under climate change. We show that the proposed adaptation strategy could save 0.31 km³ of irrigation water and 22 thousand tonnes of N fertilizer, and increase seed and food production by 33 thousand tonnes, compared with traditional practices. Significant increases in irrigation water productivity and N use efficiency can be expected by using the adaptation supporting the sustainable development of agriculture. Plain Language Summary: Food security is negatively affected by climate change, while adaptive strategies can change this situation. Grain crop production is generally used to evaluate food security. However, seed yield is often ignored and affects crop planting area and yield. To ensure food security, the government and farmers should pay more attention to the high‐yield, high‐efficiency, and sustainable development of agriculture. Hexi Corridor is a major seed‐ and grain‐producing area in China. We established an optimization‐simulation framework in Hexi Corridor for seed crop (seed maize) and grain crops (field maize), which consists of a novel crop production function and a grid‐based crop model. Considering the spatio‐temporal variability of climate and soil properties, actual crop water consumption and N uptake during each growth stage, and interactive sensitivity coefficients of water and N in growth stages under climate change, we thereby formulate an adaptive management strategy to balance the seed and food production and resource use efficiency. Our findings show that the adaptive distributed irrigation and nitrogen fertilization strategy in Hexi Corridor can ensure seed production for China's 67% field maize cultivation and adequate food production in 2021–2050, with a significant improvement in irrigation water productivity and nitrogen use efficiency. Key Points: High yield and high resource use efficiency in the Hexi Corridor can be achieved through an adaptation strategy under climate change An adaptation irrigation and nitrogen strategy can ensure future seed and food production The maize seed production under the adaptation strategy in Hexi Corridor can ensure 67% of China's field maize planting area